Super-high-resolution aerial imagery, digital surface models and 3D point clouds of the Northern Noatak Valley, Alaska - Rettelbach, Tabea; Nitze, Ingmar; Grünberg, Inge; Hammar, Jennika; Schäffler, Simon; Hein, Daniel; Gessner, Matthias; Bucher, Tilman; Brauchle, Jörg; Hartmann, Jörg; Sachs, Torsten; Boike, Julia; et al. (PANGAEA, 2024)
As part of the Perma-X airborne campaign led by the Alfred Wegener Institute in 2021, we collected super-high-resolution multispectral imagery of permafrost landscapes with the Modular Aerial Camera System (MACS), developed by the German Aerospace Center. From these images, we photogrammetrically processed four-band orthophotos (blue, green, red, near-infrared) and digital surface models at very high spatial resolution of 7 cm, as well as photogrammetric point clouds in RGB and NIR. This data collection aggregates four data subsets of the northern Noatak Valley, Alaska, covering approximately 50 km². All images were collected on 2 July 2021.
Keywords: Airborne Data; Alaska; Arctic Landscape Dynamics; Digital Surface Model; MACS; Orthoimagery; Permafrost; point clouds; Structure-from-Motion